2015
DOI: 10.1590/01047760201521031466
|View full text |Cite
|
Sign up to set email alerts
|

MORFOLOGIA DA FLOR, FRUTO, SEMENTE, PLÂNTULA E MUDA DE Cabralea canjerana (Vell.) Mart.

Abstract: MORFOLOGIA DA FLOR, FRUTO, SEMENTE, PLÂNTULA E MUDA DE Cabralea canjerana (Vell.) Mart.RESUMO: Foram realizadas coletas de material botânico de 20 árvores matrizes de Cabralea canjerana (Vell.) Mart., no Município de Frederico Westphalen, RS. Os aspectos morfológicos de flores, frutos, sementes, germinação, plântula e muda foram obtidos por meio de observações, medições e ilustrações. A inflorescência é paniculada, racimosa, com flores pequenas, hermafroditas. O fruto simples é uma cápsula septífraga, semicarn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
0
0
1
Order By: Relevance
“…The observed values for fruits and seeds biometry fit in the descriptions made by Carvalho (2003) and Felippi et al (2015b). In addition, for the physical features, Aimi et al (2016) found, for the same species, values close to those of this study and higher than those mentioned by Carvalho (2003), which mentions the presence of 1,200 seeds/Kg.…”
Section: Discussionsupporting
confidence: 90%
“…The observed values for fruits and seeds biometry fit in the descriptions made by Carvalho (2003) and Felippi et al (2015b). In addition, for the physical features, Aimi et al (2016) found, for the same species, values close to those of this study and higher than those mentioned by Carvalho (2003), which mentions the presence of 1,200 seeds/Kg.…”
Section: Discussionsupporting
confidence: 90%
“…Las flores son en Inflorescencia en panículas laterales de 5 a 15 cm de largo; 5 a 20 flores hermafroditas, blanco verdosas, de 5 a 10 mm de largo, con cinco pétalos angostos. Si bien las flores son hermafroditas, la especie se comporta como dioica, ya que, las flores femeninas tienen anteras estériles, y las flores masculinas tienen los ovarios estériles (Felippi et al 2015). Los frutos son cápsulas globosas, de 2 a 3 cm de diámetro, de color morado a rojizo, carnosas a semi-leñosas que se abren en cinco valvas (Figura 1.1.B).…”
Section: La Especieunclassified